2017
DOI: 10.1021/acs.iecr.6b04375
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Operating Parameters on the Tribological Performance of Oleic Acid-Functionalized Cu Nanofluids

Abstract: This paper reports the influence of operating parameters on the tribological performance of Cu nanofluids. The nanofluids have been prepared by blending oleic acid-functionalized Cu nanoparticles in mineral base oil and commercial multigrade lubricant. The functionalized Cu nanoparticles have been characterized by analytical techniques to ascertain chemical composition and structure of particles. The UV results indicate stable dispersion of nanofluids. The experiments have been performed to investigate the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The appearance of a stretching at 2923.9 and 2853.7 cm −1 due to the presence of −CH stretching, stretching at 1709.8 cm −1 due to the presence of CO group of carboxylic acid, and stretching at 1066.2 cm −1 due to CO group of ester. These peaks confirm the functionalization of Cu nano‐particles by oleic acid (Figure ) …”
Section: Resultssupporting
confidence: 71%
“…The appearance of a stretching at 2923.9 and 2853.7 cm −1 due to the presence of −CH stretching, stretching at 1709.8 cm −1 due to the presence of CO group of carboxylic acid, and stretching at 1066.2 cm −1 due to CO group of ester. These peaks confirm the functionalization of Cu nano‐particles by oleic acid (Figure ) …”
Section: Resultssupporting
confidence: 71%
“…The element analysis of the wear surface under lubrication of 10 W/40 CH‐4 + 0.1 wt% Cu composite lubricants is shown in Figure 12b and the detectable mass fraction of Cu is 1.65%. The antiwear and reducing friction effect is attributed to the rolling effect 47,51 caused by the ideal spherical shape and good dispersibility of the prepared Cu nanoparticles and form deposition film on the surface of the friction pair 33,36 according to the analysis of the element content.…”
Section: Resultsmentioning
confidence: 99%
“…Cu nanoparticles, as soft metal with a face-centred cubic structure, 42,43 have been favoured by researchers because of their low-shear force, excellent ductility, low-melting point, low-phase transition temperature and more environmentally friendly advantages used lubricating oil additives for reducing friction and wear. 39,41,44,45 Meanwhile, the intrinsic feature of Cu nanoparticles, such as size, 3,46 shape 3,47,48 and concentration, 43,49 are also important for excellent tribological properties. Borda et al 50 employed Cu nanoparticles that had oblong structures with sizes ranging from 10 to 30 nm as mineral oil additives for friction testing.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible reason for this result is the formation of oxidation products at 75 °C, which promotes the transition from continuous sliding to stick-slip motion. It is well reported that vegetable oil has poor stability compared to mineral oil because of the presence of unsaturated bonds, which act as active sites for many reactions, especially oxidation [33]. These unsaturated bonds lead to the formation of free radicals with the removal of hydrogen and formation of peroxy radicals, which again react with other fatty acid molecules and form hydrogen peroxide.…”
Section: Dispersion Stabilitymentioning
confidence: 99%